2020
DOI: 10.1016/j.bbrep.2020.100828
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factors SF-1 and SOX8 cooperate to upregulate Cx43 expression in mouse TM4 sertoli cells

Abstract: Gap junctions made by connexins within the adult testis are essential for communication between Sertoli cells and for spermatogenesis. Sertoli cells play an important role in supporting germ cells differentiation and maturation into spermatozoa. Connexin43 (Cx43) is the most abundant and important connexin of the testis. We have shown previously that the expression of Cx43 is being regulated by SOX and AP-1 transcription factors in Sertoli cells. However, additional regulatory elements b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In differentiated human mesenchymal stem cells, SF1 has been found to bind to FDX1 promoter and upregulate the expression of FDX1 [18,22]. cJUN has been suggested to possibly regulate the expression of FDX1 through the cyclic-AMP /protein kinase A (cAMP/PKA )pathway [19]. This study preliminarily validated that FDX1 expression is signi cantly reduced in RTECs during AKI following transfection with siRNA-SF1.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In differentiated human mesenchymal stem cells, SF1 has been found to bind to FDX1 promoter and upregulate the expression of FDX1 [18,22]. cJUN has been suggested to possibly regulate the expression of FDX1 through the cyclic-AMP /protein kinase A (cAMP/PKA )pathway [19]. This study preliminarily validated that FDX1 expression is signi cantly reduced in RTECs during AKI following transfection with siRNA-SF1.…”
Section: Discussionmentioning
confidence: 53%
“…Steroidogenic factor 1 (SF1) is a member of the nuclear receptor subfamily 5A. Studies have shown that SF1 may be involved in the regulation of other genes in cell metabolism and play a crucial role in cell proliferation, apoptosis, pyrodeath, and the regulation of mitochondrial function [18][19][20][21]. In testicular interstitial cells, increase in the dosage of SF1 through plasmid cotransfection has been shown to result in a 2.2-fold increase in ferredoxin 1 (FDX1) activators.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of Sox8 begins just prior to that of Amh in mouse testes, and SOX8 binds specifically to SOX binding sites within the Amh promoter and acts synergistically with SF1 (steroid factor 1) through direct protein–protein interaction to enhance Amh expression [17]. SOX8 and SF1 also cooperate to activate the expression of Cx43 , the most abundant and important connexin of the testis [23]. Sox8a and Sox8b, two duplicates of Sox8 identified in Japanese flounder ( Paralichthys olivaceus ), may regulate the expression of two sex hormone synthases (3 β -hydroxysteroid dehydrogenase and cytochrome P450 aromatase) by binding to their promoters directly, thereby facilitating the biosynthesis of sex steroid hormone and participating in the process of sex differentiation and gonadogenesis [9].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, NR5A1 initiates SC differentiation by directing Sox9 expression [9]. Then, it maintains page 12 Sox9 transcription and activates downstream genes by binding to cis-regulatory elements (e.g., Amh, Gja1) or synergizing through unknown mechanisms (e.g., Cyp26a1, Dhh) [16,[29][30][31][32]. As to Dmrt1, Sox8 and Ptgds, their decreased expression was also expected because SOX9 regulates their expression [17,31,33,34].…”
Section: Discussionmentioning
confidence: 99%